A Note on the Codex Angus and its Use - Costache, Doru (The journal of ecclesiastical history, 2025)
The Codex Angus (Add. MS 40 in the University of Sydney Library's Rare Books and Special Collections) is a Byzantine Gospel lectionary meant for liturgical use. The findings presented here corroborate this catalogue description. There is ample evidence of its heavy use, which indicates a public not a private setting. After a brief description of the manuscript, particularities of its content and appearance are discussed, all of which point to a small rural community, in Northern Greece, as its original owner and user. Together with introducing the codex, this article casts light on the Christian community that might have used it.